2009
DOI: 10.1303/aez.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of natural enemies in brassica crops: comparative selectivity of insecticides in the management of Brevicoryne brassicae (Hemiptera: Sternorrhyncha: Aphididae)

Abstract: In the present study, we evaluate the toxicity of six insecticides to Brevicoryne brassicae (L.) (Hemiptera: Sternorrhyncha: Aphididae), predatory coleopterans Cycloneda sanguinea (L.) (Coccinellidae) and Acanthinus sp. (Anthicidae), and the hymenopteran parasitoid Diaeretiella rapae (McIntosh) (Braconidae, Aphidiinae). Late-instar nymphs of B. brassicae and adults of C. sanguinea, Acanthinus sp. and D. rapae were exposed to nine concentrations of acephate, deltamethrin, dimethoate, methamidophos, methyl parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Despite the broad spectrum toxicity of carbamates, many authors have demonstrated the selectivity of pirimicarb to several predatory insects such as Anthicidae, Chrysopidae and Coccinellidae (Angeli et al 2005;Bacci et al 2009;Cabral et al 2008). However, laboratory as well as field studies have proven the high toxicity of pirimicarb to syrphid larvae (Colignon et al 2003;Jansen 1998Jansen , 2000Niehoff and Poehling 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the broad spectrum toxicity of carbamates, many authors have demonstrated the selectivity of pirimicarb to several predatory insects such as Anthicidae, Chrysopidae and Coccinellidae (Angeli et al 2005;Bacci et al 2009;Cabral et al 2008). However, laboratory as well as field studies have proven the high toxicity of pirimicarb to syrphid larvae (Colignon et al 2003;Jansen 1998Jansen , 2000Niehoff and Poehling 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The cabbage aphid, Brevicoryne brassicae (Homoptera: Aphididae), in particular causes serious yield loss in cabbage crops, not only because of the severe feeding damage (Bacci et al 2009), but also because of the high population densities they may reach on cabbage plants (Costello and Altieri 1995;Liu et al 1994). Several natural enemies of the cabbage aphid are reported to occur in brassica crops, which can play an important role in the suppression of the aphid population.…”
Section: Introductionmentioning
confidence: 99%
“…This difference is due to greater penetration of these molecules into the insect's cuticle. [27][28][29] However, this has not been noted here as the solubility and molecular weight of the amides were not related to their insecticidal activities.…”
Section: Toxicity Of the Substances To The Insect Pest A Monustementioning
confidence: 67%
“…The mortality of pest and predator determined in the insecticide selection and physiological selectivity bioassays, respectively, were analyzed using Student's t ‐test ( P < 0.05). We considered the insecticides that showed physiological selectivity to the predator to be those that caused higher mortality to the pest than to the predator . The mortalities from insecticides and insecticide + synergist combinations were analyzed using Student's t ‐test ( P < 0.05)…”
Section: Methodsmentioning
confidence: 99%
“…The insecticides that are used in pest management programs must be effective in controlling pests and have a low impact on non‐target organisms, such as natural enemies. Determining the residual period of control for an insecticide is essential to plan insect management strategies, which will influence the spraying frequency and, in turn, affect pest control costs . In addition to being efficient in controlling pests, each insecticide must possess a different mechanism of action to avoid the pressure of pest population selection for insecticide resistance …”
Section: Introductionmentioning
confidence: 99%